1962
DOI: 10.1126/science.137.3523.38
|View full text |Cite
|
Sign up to set email alerts
|

Clams as Indicators of Strontium-90

Abstract: Fresh-water clams concentrate strontium-90 in their shells and may be used as indicators of the Sr(90) contamination of their environment. Analysis of data derived from the specific activity of Sr(90) in shells showed that Sr(90) released to the Tennessee River system remained in solution and that concentrations to a distance of 500 miles from the release site can be predicted on the basis of the dilution of contaminated White Oak Creek water by uncontaminated Clinch-Tennessee River water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1965
1965
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Not only does stable strontium compete with radiostrontium (Sr90 ) for exchange sites, but both forms compete with the much more abundant calcium. Nelson (1962) measured the ratio of radiostrontium to stable strontium in clamshells in the Clinch River and the Tennessee River and reported that the ratio decreased with distance downstream from the mouth of Whiteoak Creek in the same manner as that predicted on the basis of flow dilution. This relationship is apparently the result of the proportional substitution of radiostronium and stable strontium for some of the calcium ions in the calcium carbonate of the clamshell as the shell is formed.…”
Section: Chemical Characteristicsmentioning
confidence: 73%
“…Not only does stable strontium compete with radiostrontium (Sr90 ) for exchange sites, but both forms compete with the much more abundant calcium. Nelson (1962) measured the ratio of radiostrontium to stable strontium in clamshells in the Clinch River and the Tennessee River and reported that the ratio decreased with distance downstream from the mouth of Whiteoak Creek in the same manner as that predicted on the basis of flow dilution. This relationship is apparently the result of the proportional substitution of radiostronium and stable strontium for some of the calcium ions in the calcium carbonate of the clamshell as the shell is formed.…”
Section: Chemical Characteristicsmentioning
confidence: 73%
“…It is well known that aquatic organisms can incorporate and concentrate radionuclides, e.g., the accumulation of strontium-90 in the shells of mollusks (Boroughs, Chipman and Rice 1957;Nelson 1962). Brother L. George, FSC.…”
Section: Results and Drscussronmentioning
confidence: 99%
“…released from ORNL tend to remain in solution, are rapidly diluted in the Clinch River and Watts Bar Reservoir, and, for the most part, flush through the system (Nelson 1962, Cowser et al 1966 Resuspension and redeposition also result in the transport of fine sediment particles downstream and f_om shallower to deeper portions of basins (e.g., Davis 1968Davis , 1973Kimmel 1978) Parker et al 1966, Pickering et al 1966, Carrigan 1969, Oakes et ai. 1982b).…”
Section: Introductionmentioning
confidence: 99%